Kebijakan Kriminal Dalam Perlindungan Korban Pelecehan Seksual Via Virtual Reality - Ramis, Teresia Avilla; Manuain, Orpa G; Fanggi, Rosalind Angel (Artemis Law Journal, 2025)
Technological advances have created virtual reality that allows for digital interaction, but also opens up opportunities for sexual harassment. Positive law in Indonesia does not yet have specific rules to regulate cases of sexual harassment in the context of virtual reality. This research aims to find out and analyze criminal policy, namely penal policy and non penal policy in the protection of potential victims of sexual harassment via virtual reality. This research is a normative legal research with a legislative, conceptual, and case approach. The source of legal materials used consists of primary, secondary, and tertiary legal materials. The technique of collecting legal materials is carried out through literature studies. Criminal policy analysis in the criminal act of sexual harassment via Virtual Reality is carried out using descriptive analysis techniques, which involve the analysis of penal policy and non penal policy to understand the applicable criminal law policy and find out preventive measures that can be used to protect potential victims of sexual harassment via virtual reality in the future. Based on the results of the research, criminal law policy in Indonesia can provide protection for potential victims of harassment via virtual reality. However, the implementation of penal policy alone is not enough, so there needs to be a non-penal policy that can help prevent and handle sexual harassment via virtual reality. Thus, criminal law policy or penal policy and non-criminal law policy or non-penal policy can be an effective solution to protect victims of sexual harassment via virtual reality.